Land inventory as a prerequisite for effective land resource management - Butenko, E.; Danshova, A.; Yurchenko, I. (Land Management, Cadastre and Land Monitoring, 2020)
This article discusses the issue of land inventory. It is noted that land inventory is one of the main means of ensuring effective land management. In addition, the problems that can be solved by land inventory for the effective management of land resources are demonstrated. It is stated that land inventory is a certain tool for land policy through land monitoring, which allows to identify inconsistencies in land use and land condition. It was revealed that the main purpose of the inventory is to create an information basis for maintaining the state land cadastre, control over land use and registration of land plots. It is considered that the clarification of the legislative regulation of land inventory will contribute to the quality of state management of land resources of Ukraine. The article explored two objects. The current state of use of their lands is analyzed. As a result, ways to solve the problems that exist in the use of land of the State Enterprise «Experimental Farm  «Victory» Volyn State Agricultural Research Station of the National Academy of Agrarian Sciences of Ukraine» and the Experimental Station of Tobacco of the National Research Center «Institute of Agriculture of the National Academy of Agrarian Sciences of Ukraine».Key words: land inventory, land resources management, State Land Cadastre, land relations, State Register of Real Property Rights, land use.